2018
DOI: 10.1111/ggi.13521
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the mediterranean diet and sleep in older adults: Results from the hellenic longitudinal investigation of aging and diet study

Abstract: The present results suggest that sleep quality is associated with MeDi adherence in older adults; there are also age-specific associations between sleep quality and the MeDi. Although additional studies are required, improvements in diet quality should be considered in the context of sleep management interventions in older individuals. Geriatr Gerontol Int 2018; 18: 1543-1548.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 31 publications
3
61
0
2
Order By: Relevance
“…These findings are in agreement with some earlier research where dietary patterns characterized with intake abundant of fruits and vegetables and legumes have been associated with better sleep quality and less sleep disturbances [5,6] In addition, our finding on fish intake and 1 The statistical significance of the hypotheses of linearity was evaluated for a trend using ANOVA for continuous variables and Cochran Armitage test for categorical variables, p value < 0.05 was taken as statistically significant; η 2 = strength of association sleep is in agreement with a study reporting an association between higher fatty fish intake and better sleep quality in participants > 40 years of age [7]. In the Hellenic Longitudinal Investigation of Aging and Diet Study, Mediterranean dietary pattern characterized by high fruit and vegetable, legume and fish intakes was also associated with better sleep quality in people > 75 years of age [23].…”
Section: Discussionsupporting
confidence: 82%
“…These findings are in agreement with some earlier research where dietary patterns characterized with intake abundant of fruits and vegetables and legumes have been associated with better sleep quality and less sleep disturbances [5,6] In addition, our finding on fish intake and 1 The statistical significance of the hypotheses of linearity was evaluated for a trend using ANOVA for continuous variables and Cochran Armitage test for categorical variables, p value < 0.05 was taken as statistically significant; η 2 = strength of association sleep is in agreement with a study reporting an association between higher fatty fish intake and better sleep quality in participants > 40 years of age [7]. In the Hellenic Longitudinal Investigation of Aging and Diet Study, Mediterranean dietary pattern characterized by high fruit and vegetable, legume and fish intakes was also associated with better sleep quality in people > 75 years of age [23].…”
Section: Discussionsupporting
confidence: 82%
“…Diet composition is a critically important contributor to US public health, as those at greatest risk for obesity and related costly chronic diseases are also those with the poorest-quality diets (41). Importantly, people who adhere to more of a Mediterranean than Western diet pattern have other characteristics that may contribute to human health, including higher levels of physical activity, sleep quality, and education and income level, and they have been reported to smoke less (42)(43)(44)(45). The data reported here suggest that diet composition itself is an important contributor to the healthy function of multiple systems involved in energy metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it has been observed that many health-related behaviors do not occur within individuals by chance, but rather they cluster [ 44 ] and may be interrelated. For example, a high diet quality has been associated with better sleep quality and lower risk of significant changes in sleep duration [ 45 , 46 ]. In this regard, the use of a TLI may even consider potential mediation effects and capture such clustering when used to predict a health-related outcome.…”
Section: Discussionmentioning
confidence: 99%